KEDUDUKAN STRATEGIS KEPEMILIKAN INSTITUSIONAL DALAM MEMODERASI PENGARUH CADANGAN KERUGIAN PENYUSUTAN NILAI TERHADAP NILAI INDUSTRI - Yustinus Kabak; Muh. Irvan Nur’ iva; Rahayu, Rahayu; H. Herman H (Yayasan Nusantara Hasana Berdikari, 2026)
This reseaccrh determines the extent to which allowance for impairment losses (CKPN) impacts firm value within the banking subsector, while also examining whether institutional ownership serves as a moderating variable in this correlation. Secondary data were sourced from the annual reports of banking firms listed on the Indonesia Stock Exchange (IDX). Through a purposive sampling approach, 123 observations were selected as the study sample. Panel data regression was employed to explore the relationships between variables. The findings reveal that CKPN exerts a positive and significant influence on firm value, suggesting that an increase in credit loss reserves tends to be interpreted by investors as evidence of sound and cautious risk management practices. Nevertheless, institutional ownership was not found to significantly moderate the CKPN–firm value relationship. This research enriches the body of knowledge in financial accounting and corporate governance, particularly with regard to the adoption of PSAK 71 on impairment loss provisioning and market reactions in Indonesia. The results are also expected to offer guidance for the Financial Services Authority (OJK) in crafting policies that promote transparent financial reporting, adherence to accounting standards, and the long-term stability of the banking industry.